Analyzing the Need for a Library Application at Madrasah Ibtidaiyah (MI) Azharyah Palembang with Recommendations - Mutiara, Choiriyah; Imam, Solikin (INTI International University, 2024)
This study aims to analyze the need for library applications and come out with solutions on the design for developing a library application at Madrasah Ibtidaiyah (MI) Azharyah Palembang. The need should cater to enhancing efficiency in library management and facilitating access to learning resources for both students and teaching staff. The application development process involves user needs analysis, system design, software implementation, and testing in a real-world environment. The research method employed in this study is The Analysis, Research, and Development (ARD) with an Agile approach, allowing flexibility in adapting application features according to user requirements. The research findings indicate that the developed library application accelerates administrative processes, such as recording book loans and returns, and includes a search feature that simplifies user access to the book collection. Application testing revealed a high level of user satisfaction, although some feedback was provided for improvements in features and the user interface. Therefore, this application is expected to be an effective solution in achieving more modern and efficient library management at MI Azharyah Palembang.